How Chanel adapted its storytelling to the digital era within its masstige segment : a case study of the perfume Chanel number 5 - Montandon, Isabelle Gomes de Amaral (2021)
The information and communication technologies - which became popular worldwide since the 1990s - have transformed the contemporary world; thus, altering interpersonal, labor and consumption relationships. Thanks to the connectivity and interaction between people, without limits of time and space, the collectivity was empowered. In this globalized world - with an endless supply of possibilities, experiences, information and products - it is crucial to offer users great content to stand out in the crowd. In this context, nothing is more effective than using storytelling to involve and engage consumers. Stories arouse interest and empathy for brands, as well as for the values they transmit; thus, strengthening emotional bonds with customers and consequently increasing the desire of purchasing their products. Luxury brands are aware of the relevance of engaging customers and creating emotional bonds. This research is a case study of the perfume Chanel Number 5, that consists of a one single phase; which is the qualitative content analysis of all advertising films the perfume, released from 1973 to 2020. This study investigated the evolution of the storytelling of Chanel - within its masstige segment - and how it has adapted to the digital age. Another objective was having a broader understanding of the use of storytelling in the advertisement of luxury and masstige brands, specially in the new digital context. The storytelling of Chanel Number 5 evolved over time and accompanied the technological changes that transformed the contemporary society; but, without ever losing its essential attributes, like glamour, luxury, allure and singularity.